Bismuth-Containing Alloys and Nanostructures - Wang, Shumin; Lu, Pengfei (Springer Series in Materials Science,, 2019)
This book focuses on novel bismuth-containing alloys and nanostructures, covering a wide range of materials from semiconductors, topological insulators, silica optical fibers and to multiferroic materials. It provides a timely overview of bismuth alloys and nanostructures, from material synthesis and physical properties to device applications and also includes the latest research findings. Bismuth is considered to be a sustainable and environmentally friendly element, and has received increasing attention in a variety of innovative research areas in recent years. The book is intended as a reference resource and textbook for graduate students and researchers working in these fields. .